Commitment to Serve the Broader Community: The Status of Linkages of a Private University in the Philippines - Briones, Jesus P. (American Journal of Social Sciences and Humanities, 2019)
This study investigated the status of the established university-industry-government linkages of the private university in the Philippines relative to its commitment of serving the broader community. The study examined the characteristics of the university’s linkages in terms of sectoral groupings of the institutions under linkage tie-ups, nature of collaboration, level of collaboration, and documentation process employed. The study also described the other linkages the university has actively participated to further achieve its commitment of serving the broader community. Using the university’s Registry Form on Linkages, it was found out that majority of its partners are coming from the industry sector, provincial-based, with OJT/ apprenticeship as the most common nature of collaboration, and where the linkages are either forged with or without MOAs/ MOUs. This private university has also tie-ups with provincial-based organizations with missions of either protecting the environment and/or improving the lives of its community residents by addressing their needs, conditions, and aspirations. While the university’s existing linkages are good enough to meet its objectives, however its current practices may still need improvement so as to fully maximize the intended benefits of its collaboration.